Lithuanian children on the internet: A comparison of the use of internet in 2010 and 2018 - Grigutytė, Neringa; Raižienė, Saulė; Pakalniškienė, Vilmantė; Povilaitis, Robertas (Psichologija, 2018)
The accessibility of the internet and the availability of online services in Lithuania are steadily increasing; the demand for some services is almost twice the EU average and is growing every year. In the context of Europe, Lithuania is among the countries with high internet use, which increases the risk and threat to children through the internet. In a study conducted by the EU Kids Online II in 2010, it was found that Lithuanian children lack the skills of safe use of internet, while parents lack the knowledge and ability to ensure the safe use of internet by their children. The purpose of this article is to identify how children’s threats and the involvement of parents in ensuring the safe use of internet by their children are changing as the access to information technology and the internet grows. During a survey conducted in 2018, 1 012 children aged 9 to 17 years and one of each of their parents were interviewed. These data were compared to the data from 2010 survey, when 1 004 online users aged 9 to 16 years and one of each of their parents were interviewed. The results revealed that in 2018, children and their parents spend more time on the internet. Children spend 4–5 hours on the internet every day and it is approximately one hour longer than in 2010. Children use a variety of devices to connect to the internet and use the internet to perform various activities, especially the sharing of pictures, watching videos and playing games on the internet, and more often use social networks sites. The most popular social network is Facebook. In the current year, children are less likely to share their personal information, communicate less with strangers, but children experience more abusive behavior from others online and have more access to sexual content in 2018 than in previous years. Parents report less negative experience and technical threats, such as the use of a child’s personal information or device infection with a virus, regarding their children spending their time on the internet. The data suggests that parents nowadays seldom are in the same room with the child while he/she is on the internet, but parents talk with children on safety issues, encourage them and are interested in their activities on the internet more often than in previous years.